Contribuições do sistema didático Galperin, Talízina e Majmutov para formação da habilidade de resolver problemas discentes em cálculo diferencial e integral em estudantes de Matemática-Licenciatura da Universidade Federal de Pernambuco - Oliveira, Naralina Viana Soares da Silva (2021)
The Brazilian educational system increasingly demands professionals who contribute to the development of the student's integral personality, passing through the formation of conceptual, procedural and attitudinal knowledge. The reality of the labor market, as well as official national documents in the educational field (BNCC, DCN and others) require this training, especially with regard to the student's ability to solve problems. Therefore, we sought to investigate the development of problem solving skills. In this perspective, the concept of problem was adopted in this study, according to Majmutov, who argues that a task can be transformed into a student problem when this task leads them to think, to reason, that is, when in the task there is an objective contradiction between the knowledge already mastered by him (known) and the knowledge to be mastered (unknown). Aiming to develop and re-elaborate the orientation of problem solving skills, problem solving was sought as a teaching methodology, which considers that the starting point of the teaching and learning process should be the problem situation and the contents as a need for solve the student problem. In this sense, the main objective of this study was to analyze the contribution of using the Student Problem Situations Activity as a teaching methodology for the reformulation of the problem-solving skill orientation in the Differential and Integral Calculus of students of the Mathematics Degree at the University Federal of Pernambuco. The aforementioned methodology, Student Problem Situations Activity, is guided by the objective of solving student problems, in the zone of proximal development, in a teaching-learning context, in which there is an interaction between the teacher, the student and the task with a problematizing character for transit through the stages of formation of mental actions according to Galperin and mediated by Talízina's theory of direction of study activity. The Student Problem Situations Activity is formed by the actions of understanding the student problem, building the conceptual and procedural core, solving the student problem and analyzing the resolution. The methodological character of the research is qualitative and quantitative, which is organized into four stages: the diagnosis of the students' initial level, the planning of the training experience, the realization of the training experience and the analysis of the process and results. The instruments and techniques for data collection were assessments (diagnostic, formative and final) and observations, based on analysis categories considered by the didactic system. In the initial diagnosis, the students showed few skills in solving a mathematical problem involving functions. After carrying out the formative experience, it was observed that approximately 65% of the class presented a reduction in the explanation in their final guiding base, with signs of generalization, little sharing and awareness. However, 35% of the class showed a base with details in the explanation, not generalized, shared and conscious.